Methodology for Measuring the Dose Rate of Pulsed Bremsstrahlung Radiation using Gamma Radiation Dosimeters with Geiger-Muller Counter - N. V. Titov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Industrial monitoring of pulsed bremsstrahlung radiation is associated with a number of challenges. Russia produces only three dosimeters that can be used for measuring pulsed bremsstrahlung radiation with a pulse duration of less than 10 gs. These dosimeters, in addition to being rather expensive, have a number of significant restrictions on the energy range (10 MeV) and the minimum pulse duration (10 ns). The DKG-RM1621 dosimeter with a Geiger-Muller counter can be used for dosimetry of photon radiation with energies up to 20 MeV. However, this device is not intended for dosimetry of pulsed radiation.Aim. Development of a methodology for conducting radiation monitoring of pulsed bremsstrahlung radiation sources using dosimeters with Geiger-Muller counters.Materials and methods. In 2021, measurements of the dose rate of pulsed bremsstrahlung radiation with a maximum energy of 3.0 MeV at pulse repetition rates of 50, 100, 150, 200, 250, 300, and 400 Hz were carried out using DKS- AT1123 (as a reference) and MKS-AT117M dosimeters with a Geiger-Muller counter.Results. A technique was developed for correcting the results of measuring the dose rate of pulsed bremsstrahlung radiation by a dosimeter equipped with a Geiger-Muller counter, which allows the dose rate of pulsed bremsstrahlung radiation to be measured with an additional error of less than 15 % in a practically significant range of dose rates. For the MKS- AT117M dosimeter at a pulse repetition rate of 400 Hz, this value was 320 gSv/h, which is sufficient for most practical tasks in radiation monitoring.Conclusion. The feasibility and possibility of successful application of dosimeters with Geiger-Muller counters for dosimetry of pulsed bremsstrahlung radiation using the proposed measurement technique with a limitation on the maximum measured dose rate is shown.